Bioprocess Development of an Extremophilic Methanotroph and Microalgae Coculture for the Production of a Novel Proteinaceous Biofeed - Cartín Caballero, Carlos Manuel (2022)
Cartín Caballero, C.M. (2022). Bioprocess Development of an Extremophilic Methanotroph and Microalgae Coculture for the Production of a Novel Proteinaceous Biofeed. [Doctor in Philosophy in Chemical and Process Engineering]. University of Canterbury, Nueva Zelanda.